Karateristik Tumbuh Kembang Siswa di SLBN Prof. Sri Soedewi - Hasmar, Wanti; Faridah, Faridah (Jurnal Akademika Baiturrahim Jambi, 2024)
The growth and development period is a very important period, because growth and development influences and determines the child's future abilities. At this time fine motor skills, gross motor skills, language, creativity, social awareness, emotional awareness, intelligence and psychological development are greatly influenced by the environment and interactions between children and their parents. Physical development is the basis for the child's subsequent developmental progress. The aim of this research is to find out the description of the growth and development of elementary school children at SLBN Prof Sri Soedewi. This research method is descriptive research to find out a picture of the growth and development of children with disabilities in State Special Schools in Jambi City. The sample for this study was 43. Analysis of the secondary data collected. The results of this research are the type of disability of children with special needs who are deaf, there are 9 students, the social development of independence is in the doubtful category, there are 19 students, the gross motor development of respondents is in the doubtful category, there are 19 students, the gross motor development of respondents is in the deviation category, there are 18 students, the development of speech and the language of respondents in the doubtful category was 20 students. It is hoped that further research suggestions can complement this research by describing other disabilities using other data collection methods.